Neural stem cells transplanted into intact brains as neurospheres form solid grafts composed of neurons, astrocytes and oligodendrocyte precursors - Karbanová, Jana; Mokrý, Jaroslav; Kotingová, Lenka (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2004)
Neural stem cells (NSCs) are tissue-specific stem cells with self-renewal potential that can give rise to neurons and glia in vivo and in vitro. The aim of this study was to transplant NSCs as whole neurospheres into intact brain and assess the fate and phenotype of their progeny generated in vivo. We isolated NSCs from E14 foetal rat forebrains and cultured them in basic fibroblast and epidermal growth factor-supplemented serum-free medium in the form of neurospheres in vitro. Neurospheres were transplanted into the intact brains of 2 Wistar rats and after a period of 3 weeks, grafted brains were examined immunohistochemically. Neurospheres formed solid grafts that were found in the lateral ventricle and in the velum interpositum under the hippocampus. The majority of cells in the transplanted tissue were identified as beta-III-tubulin(+), NeuN(+), PanNF(+) and synaptophysin(+) neurons and were accumulated throughout the graft centre. GFAP(+) astrocytes were scattered throughout the entire graft and astrocyte processes delimited the outer and perivascular surfaces. A great number of NG2(+) oligodendrocyte precursors was detected. Nestin(+) endothelial cells were found to line capillaries growing in the transplant. These data indicate that nestin(+) NSCs prevailing in neurospheres differentiate following transplantation into nestin(-) neuronal and glial cells which confirms the multipotency of NSCs. Three weeks posttransplantation neuronal and astrocyte cells reached terminal differentiation (formation of synaptic vesicles and superficial and perivascular limiting membranes) while elements of oligodendroglial cell lineage remained immature. Grafting stem cells as non-dissociated neurospheres provide cells with favourable conditions which facilitate cell survival, proliferation and differentiation. However, in the intact brain, grafted neurosphere cells were not found to integrate with the brain parenchyma and formed a compact structure demarcated from its surroundings.
Keywords: buněčná diferenciace; Oligodendroglia; Brain Tissue Transplantation; Female; krysa rodu Rattus; zvířata; neurony; Immunohistochemistry; transplantace mozkové tkáně; transplantace kmenových buněk; imunohistochemie; potkani Wistar; ženské pohlaví; Rats, Wistar; Astrocytes; Cell Differentiation; Neurons; Rats; Stem Cell Transplantation; Animals; astrocyty; oligodendroglie